(untitled) (Libya Journal of Geographical Studies, 2025)
The phenomenon of urbanization has witnessed significant development across all countries of the world, as cities have become attractive areas for populations due to the wide range of services and facilities they offer (education, healthcare, culture, roads, diverse infrastructure, etc.), in addition to employment opportunities resulting from the diversity of economic activities (industry, commerce and services, tourism, transport, etc.). Mauritania, too, has experienced considerable urban development due to both geographical and historical factors. The number of cities has increased fivefold between 1962 and 2000. This study aims to highlight the context and outcomes of the development of the urbanization phenomenon in Mauritania, tracing the evolution of urbanization before, during, and after the colonial period, while also examining the factors and consequences of urban growth in the country.